Eimeria sciurorum (Apicomplexa, Coccidia) From the Calabrian Black Squirrel (Sciurus meridionalis): An Example of Lower Host Specificity of Eimerians - Kvicerova, Jana; Hofmannova, Lada; Scognamiglio, Francesca; Santoro, Mario (Frontiers in Veterinary Science, 2020)
Host specificity plays one of the key roles in parasitism. It affects the evolution and diversification of both host and the parasite, as well as it influences their geographical distribution, and epidemiological significance. For most of parasites, however, host specificity is unknown or misrepresented because it is difficult to determine it accurately. Here we provide the information about the lower host specificity of Eimeria sciurorum infecting squirrels, and its new host record for the Calabrian black squirrel Sciurus meridionalis, a southern Italian endemic species.